Equivalent strain failure criterion for multiaxially loaded incompressible hyperelastic elastomers. (July 2019) - Rosendahl, P.L.; Drass, M.; Felger, J.; Schneider, J.; Becker, W.
Graphical abstract: Abstract: An analysis of distortional, i.e. constant volume, bulk material failure of incompressible hyperelastic elastomers in multiaxial loading conditions is presented. The present work describes deformation-based failure surfaces in terms of strain and stretch because stress-based descriptions render impractical. Classical as well as generalized strain and stretch-based failure criteria are reviewed regarding their suitability for hyperelastic polymers in their entropy-elastic regime. Classical criteria, such as the normal strain hypothesis or a von Mises-like strain criterion, prove inadequate for hyperelastic elastomers. Instead, the present work proposes a strain-based formulation of the generalized Podgórski–Bigoni–Piccolroaz criterion. This reformulation allows for an accurate description of failure surfaces of natural and synthetic rubber, filled and unfilled vulcanizates as well as silicones. It describes the failure surface in a single equation and can be readily implemented in finite element codes. For parameter identification, standard tests of soft polymers such as bulge test, uniaxial tension or planar tension test can be used.